Preparação e caracterização de pós cerâmicos de aluminatos de lítio - Ribeiro Roberto Ananias (Química Nova, 2001)
The preparation of gamma-LiAlO2 by coprecipitation and sol-gel synthesis was investigated. Ceramic powders obtained by coprecipitation synthesis were prepared from aqueous solutions of aluminum and lithium nitrates using sodium hydroxide as precipitant agent. By sol-gel synthesis, the ceramic powders were prepared from hydrolysis of aluminum isopropoxide. The materials obtained by two routes of synthesis were dried at 80ºC and calcined at 550, 750, 950 and 1150ºC. The characterization was done by X-ray diffraction, infrared spectroscopy, emission and absorption atomic spectrometry, helium picnometry, specific surface area (BET method) and scanning electronic microscopy. Mixtures of crystalline phases were obtained by coprecipitation synthesis: 80ºC- LiAl2(OH)7.2H2O + Al(OH)3; 550 and 750ºC- alpha-LiAlO2 + eta-Al2O3; 950 and 1150ºC- gamma-LiAlO2 + LiAl5O8. Chemical analysis showed molar ration Al/Li @ 3. Crystalline single-phases were obtained by sol-gel synthesis above 550ºC: 550ºC-alpha-LiAlO2; 750, 950 and 1150ºC-gamma-LiAlO2. These powders presented molar ration Al/Li @ 1. Thus, gamma-LiAlO2 crystalline phase was obtained at 750ºC by sol-gel synthesis while by coprecipitation synthesis, a mixture of crystalline phases was obtained. These results showed the superiority of the sol-gel synthesis for the preparation of pure gamma-LiAlO2.